Ni-Catalyzed Reductive Arylcyanation of Alkenes - Li, Hengxu; Chen, Jiachang; Dong, Jueqi; Kong, Wangqing (Organic letters, 2021)
We disclose a Ni-catalyzed reductive arylcyanation of alkene using environmentally benign and nontoxic organo cyanating reagent N-cyano-N-phenyl-p-toluenesulfonamide. This reaction provides a new method for the rapid synthesis of cyano-substituted oxindoles and isoquinoline-1,3-diones and features high functional group tolerance. In addition, an enantioselective version was developed for the construction of enantiomerically enriched 3-cyanomethyl oxindole. This method has also been applied to the synthesis of natural alkaloids (+)-esermethole and (+)-physostigmine.